Pengaruh Penggunaan Media Gambar Terhadap Motivasi Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas VIII SMP Negeri 1 Sipoholon Tahun Pembelajaran 2023/2024 - Yenni Pranita Nababan; Ibelala Gea; Raikhapoor Raikhapoor; Rusmauli Simbolon; Masniar H. Sitorus (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
The study aims to determine the positive and significant influence between the use of image media on the motivation to learn Christian Religious Education and Ethics of grade VIII students of SMP Negeri 1 Sipoholon for the 2023/2024 Learning Year. Descriptive and inferential quantitative research methods. The population of all grade VIII students of SMP Negeri 1 Sipoholon for the 2023/2024 Learning Year who are Protestant Christians is 160 people. Random sampling is 25% of the total population, which is 40 people. The research instrument is in the form of a closed questionnaire. The results of the data analysis were obtained: a) The value of rhitung=0.553>rtabel=0.312 and thitung=4.091>ttabel=2.021 shows a relationship between the use of image media and learning motivation Christian Religious Education and Ethics of grade VIII students of SMP Negeri 1 Sipoholon Learning Year 2023/2024. b) Regression equation . c) The determination test is known to have an effect of 30.58%. d) Test the hypothesis obtained Fcalculate = 16.693 > Ftable = 3.23 then H0 is rejected and Ha is accepted. The study concluded that there is a positive and significant influence between the use of image media on the motivation to learn Christian Religious Education and Ethics of grade VIII students of SMP Negeri 1 Sipoholon for the 2023/2024 Learning Year.